Crimes by Visitors Versus Crimes by Residents: The Influence of Visitor Inflows - Boivin, Rémi (Journal of quantitative criminology, 2018)
To disaggregate the crime impact of visitor inflows. There is increasing evidence that visitors can make a major contribution to levels of crime in a given neighbourhood: crimes by visiting offenders may add to those committed by local offenders, while visitors (and their property) may provide local offenders with additional opportunities for crime.